Severe Heterotopic Ossification following Total Knee Replacement - Alexander L. Dodds; Gregory C. R. Keene (Case Reports in Orthopedics)
Although the incidence of minor heterotopic ossification is probably higher than what is usually expected, severe heterotopic ossification (HO) is an extremely rare event following total knee replacement surgery. We present the case of a 66-year-old woman who initially had achieved an excellent range of motion following bilateral uncemented rotating platform total knee replacement, before presenting with pain and loss of range of motion at 2 months after surgery. Severe HO was diagnosed on X-rays. Treatment consisted of nonoperative measures only, including physiotherapy with hydrotherapy and anti-inflammatories. She eventually regained her range of motion when seen at 8 months after operation. This case illustrates that nonoperative treatment without the use of radiotherapy or surgery can be used to safely resolve stiffness caused by HO after total knee replacement.